Electronic Coupling of Single Atom and FePS3 Boosts Water Electrolysis. Issue 3 (8th July 2021) - Tang, Chongyang; He, Dong; Zhang, Nan; Song, Xianyin; Jia, Shuangfeng; Ke, Zunjian; Liu, Jiangchao; Wang, Jianbo; Jiang, Changzhong; Wang, Ziyu; Huang, Xiaoqing; Xiao, Xiangheng
Abstract : Engineering the electronic structure of surface active sites at the atomic level can be an efficient way to modulate the reactivity of catalysts. Herein, we report the rational tuning of surface electronic structure of FePS3 nanosheets (NSs) by anchoring atomically dispersed metal atom. Theoretical calculations predict that the strong electronic coupling effect in single‐atom Ni‐FePS3 facilitates electron aggregation from Fe atom to the nearby Ni‐S bond and enhances the electron‐transfer of Ni and S sites, which balances the oxygen species adsorption capacity, reinforces water adsorption and dissociation process to accelerate corresponding oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). The optimal Ni‐FePS3 NSs/C exhibits outstanding electrochemical water‐splitting activities, delivering an overpotential of 287 mV at the current density of 10 mA cm −2 and a Tafel slope of 41.1 mV dec −1 for OER; as well as an overpotential decrease of 219 mV for HER compared with pure FePS3 NSs/C. The concept of electronic coupling interaction between the substrate and implanted single active species offers an additional method for catalyst design and beyond. Abstract : Iron thiophosphates (FePS3 ) anchored by atomically dispersed metals (Ni, Co, Pd) were synthesized as robust water splitting electrocatalysts. The strong electronic coupling effect in single atom Ni‐FePS3 facilitates electron aggregation from Fe atom to the nearby Ni‐S bond and enhances the electron‐transfer of Ni and S sites, which balances the oxygen species adsorption capacity, reinforces water adsorption and dissociation process to accelerate corresponding OER and HER.